Boring Holes: The Crystalline Body of Beckett's The Lost Ones. Issue 1 (April 2018) - Rada, Michelle
Abstract : In a 1937 letter to Axel Kaun, Beckett describes the mark of modern literary ambition as an inexhaustible drive to 'drill one hole after another into [language] until that which lurks behind, be it something or nothing, starts seeping through.' Much is made of this little line by readers of Beckett from Gilles Deleuze and Mladen Dolar to, more recently, Alenka Zupançiç. As its title teases, this essay takes up Beckett's directive to read for, with, and through the holes bored into language alongside the bodies—narrated and narrating—captured by it as so many boring, banal holes into which meaning, form, and other bodies can be pushed. In The Lost Ones, Beckett's short prose piece from 1971, bodies abound: lost, scurrying, shivering, defeated, sweaty, aroused, pained, aging, nauseated, desiring bodies. Beckett's 'most anthropological work, ' as C. J. Ackerley and S. E. Gontarski have dubbed it, The Lost Ones proposes a series of fundamental contradictions or antagonisms between the narrating 'anthropological' voice concerned with quantitatively capturing a neutralized (and neutered, disembodied) totality—and the titular 'lost' bodies that inhabit the world of the text, for whom embodiment wholly determines both the potentialities and limitations of life, movement, and feeling. The 'bore' of a cylinder—the shape of the contained world of The Lost Ones —incidentally also names the diameter of empty space, the hole, around which its form wraps. This essay explores the antagonistic relationship between the circumscribing forces that envelop and contain life in the cylindrical space of narration, and its bore: the 'something or nothing, ' as Beckett might put it, into which a substance can drill, enter, flood, leak, or fall. The objectifying impulses of the affectively eviscerating, abstracted narrator of The Lost Ones short-circuit throughout the text in special moments, when the bodies the voice describes erupt into what this essay will call a 'crystal image.' Taken from Deleuze's Cinema books, the crystal image and its transmission through 'crystalline description' name a set of aesthetic operations through which antagonisms can coexist. In other words: where otherwise mutually exclusive contradictions appear simultaneously as imbricated conditions of possibility for a single image. While the voice gazes, god-like, from above the cylinder, the bodies it describes explode its forms of containment with a kind of qualitative surplus that over and again impedes the narrator's attempts to totalize, circumscribe, and define the limits of embodied and affective life. I argue that the eruption of affect within the scientistic descriptive mode not only forms a crystal image out of an otherwise contained realm of quantifications, but that by pinning oppositional forms of aesthetic capture and representation against one another, the text reveals fundamental contradictions at play within narration and description more broadly. These contradictions and equivocations are not to be resolved or reconciled, I argue, but animated, sparked, and put into play through the process of reading.